Results of TB contacts investigation in community during the COVID-19 pandemic in North Kalimantan Province - Khuntari, Wiwit (BKM Public Health and Community Medicine, 2021)
Objective: This study aims to describe the results of the investigation of TB contacts during the COVID-19 pandemic in North Kalimantan Province. Contact investigation is a tracking and investigative activity aimed at people who are in contact with TB patients (index cases) to find TB suspects. Method: This research uses a descriptive method. Investigations were carried out on bacteriologically confirmed TB Index cases and TB cases in children, investigations were carried out by the TB Health Center Program Manager, HC cadres, and STPI Penabulu cadres in North Kalimantan Province. Data sourced from SITB (Tuberculosis Information System) in 2020 and 2021 (Until October). Results: The number of TB cases found in North Kalimantan Province in 2020 was 963 cases, Treatment Coverage: 35%, and 2021 found 625 cases, Treatment Coverage: 23%. The highest proportion of TB cases is in Tarakan City (2020: 45% and 2021: 49%). Contact investigations during the COVID-19 pandemic were carried out by observing health protocols. The number of indexes investigated in 2020 was 321 cases with a total of 1,825 contacts,15% of the investigated contacts met the referral requirements as suspects and 94% of contacts who wanted to be referred were subjected to laboratory examinations so that the percentage of sick contacts was found TB among suspects was 21%. The number of indexes investigated in 2021 was 192 cases with a total of 937 contacts, 30% of the investigated contacts met the referral requirements as suspects and 98% of contacts who wanted to be referred were subjected to a laboratory examination so that the percentage of contacts was found TB disease among suspects by 19%. The results of the contact investigation found an additional 9 cases of TB in 2020 and 16 cases in 2021. Conclusion: The decline in TB case finding during the COVID-19 pandemic requires an active case-finding strategy in the community as an effort to find early cases for standardized management.